New faunistic records of threatened saproxylic Coleoptera, Diptera, Heteroptera, Homoptera and Lepidoptera from the Republic of Karelia, Russia - Siitonen, Juha; Martikainen, Petri; Kaila, Lauri; Mannerkoski, Ilpo; Rassi, Pertti; Rutanen, Ilpo (Entomologica Fennica, 1996)
Saproxylic insects were collected during fifteen expeditions to the Republic of Kareliain summers 1991-94. A total of 63 species (48 beetles, 15 others) included in the Finnish red data book are reported. Fourteen species of Coleoptera and Aradus ribauti Wagner are reported as new for Karelia. Notes on the biology of e.g. Hylochares cruentatus (Gyllenhal), Rhizophagus puncticollis Sahlberg, Cis fissicomis Mellié, Sulcacis bidentulus (Rosenhauer) and Leptura thoracica Creutzer are given. The number of threatened species found is striking considering the short period of time spent collecting in the field. We ascribe this to the management history of forests in Karelia, especially to the large amount of decaying wood in managed forests even. The forests in Karelia will be of crucial importance in preserving biodiversity and the last viable populations of numerous species that have disappeared in other parts of Fennoscandia.